The effect of ursolic and oleanolic acids on human skin fibroblast cells - Helena Donica; Piotr Niedziela; Anna Matysik-Woźniak; Roman Paduch; Magdalena Wójciak-Kosior (Folia Histochemica et Cytobiologica, 2012)
In this article, we look at how ursolic and oleanolic acids can be used for the purpose of quality control of natural products used in dermatocosmetology as well as of various other therapeutic preparations. Ursolic acid (UA) and oleanolic acid (OA) are pentacyclic triterpenes and they are constituents of many medicinal herbs. In this study, we analyzed the cytotoxic and anti-proliferative activity of OA and UA against normal human skin fibroblasts (HSF). Additionally, the scavenging activity of free radicals of both acids was analyzed. The sensitivity of cells to OA and UA activity was determined using a standard spectrophotometric (MTT) assay. The free radical scavenging activity of OA and UA was measured using the DPPH• test. The F-actin cytoskeletal proteins organization was analyzed using TRITC-phalloidine fluorescent staining. The cytotoxic activity of the analyzed acids was determined using Neutral Red (NR) uptake assay. Of the two isomeric compounds, UA showed a higher cytotoxic activity against HSF cells than did OA. Our investigations showed that OA, in view of its non-toxic nature, may be used as a supplementary factor for dermal preparations. (Folia Histochemica et Cytobiologica 2011; Vol. 49, No. 4, pp. 664–669)